A mezőgazdasági munkaerő változása (a Dél-Alföld és a Dél-Dunántúl összehasonlítása) - Weber, Erika (Közép-Európai Közlemények, 2014)
The share of agricultural employment is decreasing. In 1980 20% of employees, in 2005 only 5% worked in agriculture in Hungary. Before the changing of the regime, the state farms and cooperatives had significant employment potential, but nowadays they have changed or eliminated , so a significant part of previous workers have become unemployed, inactive, or they are looking for working places in other sectors of the economy. The question is whether this free labour capacity can be absorbed by agriculture nowadays. The Southern Great Plain and the Southern Transdanubia possess good conditions from the point of view of agricultural production factors. The agriculture and the related industries are playing also agreat part in economic and social life of the regions nowadays, so these regions are important areas from the point of view of agricultural labour force analyse.